How Important is Access to Jobs? Old Question - Improved Answer - Olof Åslund; John Östh; Yves Zenou (Research Institute of Industrial Economics (IFN), 2006)
We study the impact of job proximity on individual employment and earnings. The analysis exploits a Swedish refugee dispersal policy to get exogenous variation in individual locations. Using very detailed data on the exact location of all residences and workplaces in Sweden, we find that having been placed in a location with poor job access in 1990-91 adversely affected employment in 1999. Doubling the number of jobs in the initial location in 1990-91 is associated with 2.9 percentage points higher employment probability in 1999. The analysis suggests that residential sorting leads to underestimation of the impact of job access.
Keywords: J15; J18; R23; 330; Spatial Mismatch; Endogenous Location; Natural Experiment; Regionaler Arbeitsmarkt; Ethnische Gruppe; Einkommen; Beschäftigung; Schweden; Geographische Entfernung